PERSEPSI SISWA INTEGRASI MATERI PEMBELAJARAN BIOLOGI DENGAN NILAI-NILAI RELIGIUS ISLAM DI KELAS XI MADRASAH ALIYAH NEGERI SE-PADANG PARIAMAN - Maulana, Irsan; Ardi (Jurnal Biogenerasi, 2025)
The Indonesian National Education System Law No. 20 of 2003 emphasizes the importance of education in shaping individuals with faith and piety. Education in State Madrasah Aliyah (MAN) aims to integrate general knowledge with Islamic values, including in Biology learning. However, observations in MAN across Padang Pariaman Regency indicate that the integration of Islamic values in Biology learning has not been fully implemented. The main obstacles include limited instructional time, inadequate teacher understanding, and a lack of reference materials. This study aims to analyze the factors influencing students' perceptions of the integration of Islamic values in Biology learning in Grade XI of MAN in Padang Pariaman Regency. The study employs a descriptive qualitative method, with a research population consisting of all Grade XI Science students from MAN 1, MAN 2, MAN 3, and MAN Insan Cendekia, totaling 319 students. A sample of 162 students was selected using Simple Random Sampling with the Slovin formula. Primary data were collected through teacher interviews and student questionnaires. Data analysis was conducted using percentage calculations, averages, standard deviations, and categorization using SPSS 22. The findings reveal that, based on four key indicators—attention, mindset, value system, and personality type—students' perceptions of the integration of Islamic values in Biology learning fall within the good to very good category, with an average score in the good category.